Socio-economic and enviromental effects of bioenergy based on wood ine the development of remote areas - Natalia Vukovic; Andrey Mehrentsev; Evgeny Starikov (Institute of Economic Research (IER), 2017)
Traditional energy sources based on oil, coal, and natural gas have proven to be highly effective, but at the same time they have many negative environmental effects. Also by technical and economical points traditional energy sources are not available in many remote areas. In this paper, the authors have been discussed the alternative approach in energy supply, which also has positive social-economic and environmental effects. This paper provides a new solution for energy supply in remote areas by implementing bioenergy based on woodchips, which has multi-sector effects. Bioenergy generation based on woodchips has multi-sector effect that is why authors offer to combine forest cleaning cutting and forest thinning with bioenergy based on woodchips in one project which will have social, economic and ecological effects. The situation with forest fires makes the authors idea more attractive because after forest fires the problem of cleaning cutting in forest became very important and urgent by ecological and economical points: after cleaning cutting there are a lot of low quality wood which by author's idea can be recycled into chips for bioenergy. This methodology has been applied to bioenergy and regional development decisions in remote areas which mainly have a problem with energy provision; it is suitable for applications to infrastructure development projects in any remote forested region of the world. Mobile bioenergy generation based on woodchips in remote areas settle the complex of environmental, social, economic problems and can become the driver of development of the region.
Keywords: O44; P28; Q01; Q42; 330; bioenergy; woodchip; cleaning cuttings; forest thinning; remote areas development